Residential-based discrimination in the labor market - Stepan Mikula; Tommaso Reggiani (Cardiff University, Cardiff Business School, 2022)
Through a correspondence study, this paper investigates whether employers discriminate job applicants based on their living conditions. Exploiting the natural setting provided by a Rapid Re-housing Program, we sent 1,347 job applications for low-qualified front-desk jobs in Brno, Czech Republic. The resumes exogenously differed in only one main aspect represented by the address of the applicants, signaling both the quality of the neighborhood and the quality of the housing conditions in which they were living. We found that while the higher quality of the district has a strong effect in increasing the hiring chances (+20%) the actual improvement of the living conditions standards, per se, does not generate any significant positive effect.
Keywords: C93; J08; J71; 330; correspondence study; labor discrimination; housing conditions; Rapid Re-housin